Judicial Balancing of Environmental Rights and Economic Development: A Comparative Analysis of Uganda and the European Court of Human Rights Interventions - Mundeke, Moses; Okonji, Ifesinachi Charles; Afunaduula, Isaac Afuna; Adeke, Caroline; Wanbogo, David; Babirye, Tracy; Atwine, Julian; Namisi, Hope; Ozitiru, Patricia; Ndagire, Maria (NIU Journal of Legal Studies, 2026)
In developing countries such as Uganda, the pursuit of economic development including mining and extraction of oil and mineral resources usually infringe on environmental rights. The court is faced with the arduous duty of ensuring a balance in the pursuit of economic development and preservation of environmental rights. Using doctrinal research method and comparative analytical method, this article presents a comparative analysis of judicial balancing between environmental rights and economic development in Uganda and under the European Court of Human Rights. It examines how courts structure legal reasoning when environmental protection needs conflicts with economic and developmental objectives, with particular focus on constitutional provisions, statutory frameworks, and judicial interpretation. The study is guided by the research question of how different legal systems conceptualise and operationalise the balance between environmental rights and economic development in judicial decision-making. It employs a comparative analytical method to assess the laws relating to right to a clean and healthy environment, which enables direct rights-based litigation before national courts. The European Court of Human Rights has given protection of environmental interests through established human rights provisions, especially the right to respect for private and family life. The article focuses on judicial reasonings in environmental disputes and the role of courts in resolving conflicts between environmental protection and economic development within their respective legal frameworks. The article contributes to existing scholarship by moving beyond single-jurisdiction studies to provide a structured comparison between a constitutional environmental rights model, as seen in Uganda, and an indirect human rights model, as developed by the European Court of Human Rights. Keywords: Environmental Rights, Economic Development, Judicial Balancing, Proportionality, Uganda, European Court of Human Rights, Sustainable Development.